Hubungan Pola Asuh Dan Jenis Pekerjaan Ibu Terhadap Kenakalan Remaja Di Kecamatan Tanjungpinang Timur - Zuhdian, Diov Hafizh; Wahyuni, Sri; Samnuzulsari, Tri (Innovative: Journal Of Social Science Research, 2024)
The role of mother in the household is one of the important factors because the mother has the responsibility to manage the household and educate the child at hoe. a mother who works with various types of work certainly has different activities, but with this busy function of the mother in the parenting pattern of the child must be appropriate so that it can monitor the occurrence of delinquency of teenagers. The theory used to look at parenting (X1) according to Stewart and Koch's theory is authoritarian, permissive, and democratic while to discuss the work type variable (X2) using Mathis (adamy) theory and to discuss juvenile delinquency (Y) refers to Santrock's theory (2007). The purpose of this study was to find out the relationship of variables X1 to Y, X2 to Y and X1, X2 to Y. This type of study is quantitative with a correlation approach and a statistical test of SPSS version 25. Data processing uses the test of moment products. The results of the study showed that from the partial test there was a significant relationship between parenting patterns against delinquency of adolescents in East Tanjungpinang District, namely THitung 0.462 > TTabel 0.167 means that it has a strong relationship.The relationship between maternal work type and adolescent delinquency in East Tanjungpinang District was tested partially did not have a correlation because the count of 0.152 < tTable 0.167 While the results of the study simultaneously were calculated as 0.8057 >Table 0.167 means there was a significant relationship between parenting, and the type of mother work to teenage delinquency in East Tanjungpinang District. Then from the Determinant Coefficient Test (R2) processed according to the Pearson Produc formula, the moment obtained by 90%, namely the parenting variable, the parent's work type variable and the delinquency of adolescents have a high contribution from the parenting variable (authoritarian, permissive, democratic) with the interpretation value criteria (R) between 0.800-1.00 means the parenting variable is more dominant against juvenile delinquency by 90%, and the remaining 10% is influenced by other factors not studied in this study. Working mothers should pay more attention and supervision to teenagers so that they are evaded from mischievous behavior. Keyword : Parenting, Employment Type, Juvenile Delinquency